THE INFLUENCE OF LEADERSHIP STYLE, AND ORGANIZATIONAL COMMITMENT, ON EMPLOYEE DISCIPLINE AND ALSO ITS IMPACT ON EMPLOYEE PERFORMANCE OF THE DHARMASRAYA DISTRICT COMMUNITY AND VILLAGE EMPOWERMENT OFFICE - Syukri, Muhammad; Heryanto, Heryanto (Archives of Business Research, 2019)
This study attempts to examine the effect of leadership style and organizational commitment on employee discipline and its impact on the performance of the Dharmasraya District Community and Village Empowerment Office staff. This study uses descriptive quantitative methods. The study population consisted of 30 employees at the Regional Secretariat of the Dharmasraya Regency. To obtain a valid and realistic instrument have been tested the validity and reliability test. The data analysis technique used is path analysis. The results showed that leadership style and organizational commitment had a positive and significant effect on discipline and performance, as well as discipline as an intervening variable able to provide an increase in influence between leadership styles on performance. The empirical findings indicate that for the performance of the staff of the Regional Secretariat of Dharmasraya Regency, the Dharmasraya District Community and Village Empowerment Service needs to pay attention and focus more on improving leadership style factors and commitment.